2001
DOI: 10.1103/physrevb.64.094511
|View full text |Cite
|
Sign up to set email alerts
|

Joule heating induced by vortex motion in a type-II superconductor

Abstract: We present experiments that determine the temperature increase in a type-II superconductor due to Joule heating induced by vortex motion. The effect of Joule heating is detected by comparing the response of the vortex lattice to fixed amplitude current steps of short ͑10 s͒ and long ͑4 s͒ duration, where the Joule heating is negligible and saturates, respectively. The thermometry is based on the temperature dependence of the voltage response of the vortex lattice to a driving current. By monitoring the tempera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
2
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 28 publications
(40 reference statements)
2
2
0
Order By: Relevance
“…Figure 6 shows a continuous variation of I C with R N for all the superconducting samples which supports our argument that the physics evolves continuously from the BKT to the PS regime, and that extraneous effects (such as electron heating [56,57]) do not perturb the data even for p p c  . In fact, as shown by the solid line in figure 6, the data are consistent with I R…”
Section: Critical Currentssupporting
confidence: 79%
See 1 more Smart Citation
“…Figure 6 shows a continuous variation of I C with R N for all the superconducting samples which supports our argument that the physics evolves continuously from the BKT to the PS regime, and that extraneous effects (such as electron heating [56,57]) do not perturb the data even for p p c  . In fact, as shown by the solid line in figure 6, the data are consistent with I R…”
Section: Critical Currentssupporting
confidence: 79%
“…The situation is complicated further in samples with low R N (e.g. Figure 4) which exhibit sharp hysteretic jumps to the normal state so that the transition from BKT to breakdown behaviour is shown more clearly in measurements using pulsed current excitation, which eliminate the heating effects responsible for hysteresis [55] near I C [56,57]. At lower currents, pulsed current measurements are consistent with the BKT and breakdown behaviour observed using DC currents.…”
Section: Critical Currentssupporting
confidence: 59%
“…The curves all collapse onto a single curve, as shown in Fig. 3(c) , which cannot be explained by the depairing current density ( J d ) given by J d ( t ) ∝ (1 − t 2 ) 3/2 (1 + t 2 ) 1/2 (dashed line) 18 , nor by the Joule heating, J heating (Δ T ∝ J 2 ) which is caused by the contact resistance (dotted line) 19 . Rather, they collapse onto the curve expected from the δT c -pinning mechanism (solid line), J f ( t ) ∝ (1 − t 2 ) 7/6 (1 + t 2 ) 5/6 , suggesting that the temperature dependence of the FFF current density is primarily determined by spatial variations in T c (refs 20 , 21 ).…”
Section: Discussionmentioning
confidence: 95%
“…Each point is obtained on a pristine vortex lattice freshly prepared from the normal state. It was previously shown that for samples and mounting methods identical to the ones used here Joule heating effects on time scales < 10 µs are negligible 13 . In addition to avoiding heating, the pulsed technique also eliminates effects due to current induced organization as we show below.…”
mentioning
confidence: 86%